2018 21st International Conference on Intelligent Transportation Systems (ITSC) 2018
DOI: 10.1109/itsc.2018.8569282
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pedestrian road-crossing assertiveness for autonomous vehicle control

Abstract: Autonomous vehicles (AVs) must interact with other road users including pedestrians. Unlike passive environments, pedestrians are active agents having their own utilities and decisions, which must be inferred and predicted by AVs in order to control interactions with them and navigation around them. In particular, when a pedestrian wishes to cross the road in front of the vehicle at an unmarked crossing, the pedestrian and AV must compete for the space, which may be considered as a game-theoretic interaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…3) Feature selection methods: Bonnin et al [27] proposed a generic context-based model to predict pedestrians behavior according to features describing their local urban environment. To learn about interactions between autonomous vehicles and pedestrian interactions, in [37], Camara et al collected data from real-world pedestrian-vehicle interactions at an unsignalized intersection. The actions of pedestrians and vehicles were ordered into sequences of events comprising descriptive features and the study revealed the most predictive features in a crossing scenario such as the head direction, the position on the pavement, hand gestures etc.…”
Section: Event/activity Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…3) Feature selection methods: Bonnin et al [27] proposed a generic context-based model to predict pedestrians behavior according to features describing their local urban environment. To learn about interactions between autonomous vehicles and pedestrian interactions, in [37], Camara et al collected data from real-world pedestrian-vehicle interactions at an unsignalized intersection. The actions of pedestrians and vehicles were ordered into sequences of events comprising descriptive features and the study revealed the most predictive features in a crossing scenario such as the head direction, the position on the pavement, hand gestures etc.…”
Section: Event/activity Modelsmentioning
confidence: 99%
“…This is consistent with recent research [166] that reported head orientation/gaze towards vehicles as the most prominent cues for predicting pedestrian intent. In addition, computational models have shown that head direction is a useful trait for pedestrian path prediction and state of situation awareness such as in [37] which argued that if a pedestrian looks at the vehicle, they are less likely to cross the road.…”
Section: B Signalling Interaction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most basic method of sensing pedestrians is to use human perception, which is often used in offline studies, such as for conducting on-street surveys or annotate recordings of such surveys made with other sensors [29], [30]. Humans still have advantages over automated systems since they can use their full intelligence to subjectively annotate otherwise difficult events, such as the meanings of body language, emotions, and gestures.…”
Section: A Passive Sensors A) Manual Detection and Labellingmentioning
confidence: 99%
“…We collected a large scale data from real-world human road crossings at the intersection near the University of Leeds, UK. Pedestrian-vehicle interactions were decomposed into sequences of independent discrete events [9]. We looked for common patterns of behaviour that can predict the winner of an interaction, which can thus be integrated into gametheoretic AV controllers to inform real-time interactions.…”
Section: A Sequence Patterns Recognitionmentioning
confidence: 99%